Multi-dimensional analysis of In-vehicle air quality: An industry status study of benzene, formaldehyde, acetaldehyde and TVOC - Liu Danfeng; Xue Fei; Liu Yang; Cai Xiaodi; Li Qi (E3S Web of Conferences)
The concentration of volatile organic compounds (VOCs) determines the air quality in vehicles, so we build a new evaluation system based on the concentration of aldehydes, the odor of vehicles, the total VOCs (TVOCs) and other parameters to evaluate the air quality in vehicles. Though the overall air quality in the car improves rapidly in recent years, there are still challenges in the release of aldehydes and odor control in the car under the high temperature condition. First of all, in terms of benzene series, they are under a considerable control and are below the national standard limit (0.11 mg/m3) in the three-stage working conditions. Secondly, for aldehydes, the formaldehyde concentration under normal temperature and ventilation conditions is lower than the national standard limit (0.1 mg/m3), while the formaldehyde concentration under high temperature conditions generally exceeds the national standard limit. Acetaldehyde is one of the most serious pollutants exceeding the standard. The proportion of acetaldehyde exceeding the national standard limit (0.05 mg/m3) at normal temperature and ventilation conditions is 54% and 17%, respectively, and only 15% under high temperature conditions are not exceeding the standard. In addition, in terms of the odor in vehicles, the average compliance rate is as low as 76% and become inferior under high temperature conditions. Finally, in terms of TVOC, the vehicle industry lacks a unified control standard, and the concentration level of various enterprises fluctuates greatly. The average values of TVOCs in normal temperature and high temperature conditions are 2.467 mg/m3 and 8.392 mg/m3 respectively. With the increase of the temperature inside vehicles, the TVOC concentration increases to different degrees. On the basis of the existing in-vehicle air quality management standards and technical guidelines, the vehicle industry should expand the range of quality control indicators, introduce the TVOC dimension, further improve the in-vehicle air quality management, reduce health hazards, and improve the level of in-vehicle air quality management.